2015
DOI: 10.1063/1.4907572
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of thermal stresses in elastic multilayer coating systems

Abstract: The performance and reliability of multilayer coating systems are strongly influenced by thermal stresses. The present study develops an alternative analytical model to predict the thermal stresses in elastic multilayer coating systems. An exact closed-form solution is obtained which is independent of the number of coating layers. In addition, with the definition of the coordinate system, the closed-form solution is concisely formulated. Specific results are calculated for thermal stresses in HfO2/SiO2 multila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…For the stress evaluation in the Ti(C,N) and Zr(C,N) layers, an average value of the DEC for TiC/TiN and ZrC/ZrN was used, respectively. Residual theoretical and thermal stresses were calculated for each layer using Equation (2), assuming a plane-state of residual stress [22]:…”
Section: Methodsmentioning
confidence: 99%
“…For the stress evaluation in the Ti(C,N) and Zr(C,N) layers, an average value of the DEC for TiC/TiN and ZrC/ZrN was used, respectively. Residual theoretical and thermal stresses were calculated for each layer using Equation (2), assuming a plane-state of residual stress [22]:…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is concluded that the Stoney stress model is merely valid for very small thickness ratios. Moreover, as mentioned in the introduction section, the Timoshenko and Gao et al models have been developed based on the beam bending theory using the strain continuity at the interfaces of the layers (Gao et al, 2015;Timoshenko, 1925). Also, the results of the Timoshenko and Gao et al models are the same at both thickness ratios given in Fig.…”
Section: Analytical Modelmentioning
confidence: 98%
“…The width of the thin film-substrate composite is equal to 10 mm. Therefore, it is clear that the problem is multi-scale in nature (nano-sized film versus micro scale substrate with millimeter value for width of the composite) and hence Table 1 Biaxial stress relations in the thin film according to some analytical models (Gao et al, 2015;Stoney, 1909;Suhir, 1988;Timoshenko, 1925).…”
Section: Verification Of the Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Hkl A comparison of the experimentally obtained residual stress values (σ ) and the theoretical values (σ th ) was made. Since the magnitude of the total coating thickness is of micrometers (~9 µm) compared to the bulk size (5000 µm), it can be assumed that the coating is in a plane-state of residual stress and that the theoretical stress value of each single layer can be assumed to be independent of each other in the multilayer [22]. Hence, the magnitude of the thermal residual stress depends on the elastic modulus of the coating, the CTE of the layers and substrate, as well as the temperature variation.…”
Section: Componentmentioning
confidence: 99%